BIOLOGIA POPULACIONAL DE MINUCA RAPAX (SMITH, 1870) (CRUSTACEA, DECAPODA, OCYPODIDAE) EM UM MANGUEZAL DO NORDESTE BRASILEIRO - Becker, Jaqueline; Castiglioni, Daiana da Silva; Ozga, Aline Vasum; Castiglioni, Daniela da Silva (Revista Nordestina de Zoologia, 2019)
This study was conducted to characterize the population biology of the fiddler crab Minuca rapax. The following aspects were analyzed: carapace width (LC), morphological sexual maturity, frequency distribution, sexual ratio and recruitment. Samplings were performed monthly, for one year (April 2009 to March 2010), manually by two people in a period of 30 minutes during low tide of syzygy. A total of 646 males and 261 females were sampled. Males had a mean body size of carapace width (± sd) significantly higher than females (males - 14.04 ± 3.14 mm, females - 13.34 ± 2.52 mm). In the determination of morphological sexual maturity, males with 12.4 mm of LC and females with 9.9 mm of LC were considered mature (50%). Juveniles males showed a significant differential growth in the cheliped propodus length (CPL) in relation to adults. In the females, a significant difference was observed in the growth of the abdomen width (AW) between juveniles and adults. The distribution of frequency in the population of the studied species was unimodal, suggesting a stable population. It was observed the sex ratio of 1: 1, being observed 2.48 males: 1 female. In the recruitment analysis it was observed a greater number of juveniles on May while the lowest number has been registered in October, where only one specimen was sampled. The results of this study will contribute information on the biology of the species and thus provide subsidies for the conservation of the species in the Formoso River mangrove.